HUBUNGAN RIWAYAT PEMBERIAN ASI EKSKLUSIF DAN STATUS IMUNISASI DENGAN ANGKA KEJADIAN STUNTING PADA BALITA DI WILAYAH KELURAHAN KATULAMPA BOGOR - Aprilla Rahma Utaminingtyas (2023)
Stunting is a disorder in which toddlers experience body failure due to continuous malnutrition, causing children to be too short for their age. Malnutrition can occur both during pregnancy and in the first few days after birth. This study aims to determine the relationship between exclusive breastfeeding and immunization status with the incidence of stunting in toddlers aged 2-5 years in the Katulampa, Bogor. The research design used was cross-sectional. The sample in this study was 113 toddlers obtained by purposive sampling. The research was conducted from April to May 2023. Data collection was carried out by measuring height and questionnaires. Data analysis was performed with the chi-square test. The results showed that there was a significant relationship between history of breastfeeding with a p value = 0.013, and there was a significant relationship between family income and the incidence of stunting with a p value = 0.018. From this research, it is hoped that the government, especially health workers, will be able to actively tackle the incidence of stunting in toddlers. In addition, it is hoped that the community will be able to implement a balanced nutritional diet for toddlers.